The use of genetic, manual and chemical methods to control pollination in vegetable hybrid seed production : a review - Colombo, Noemi; Galmarini, Claudio Romulo (2017)
Production of hybrid varieties of vegetable crops is currently a desired breeding goal, due to their remarkable agronomic performance and to the possibility of intellectual property protection. However, efficient hybrid production requires a careful pollination control to guarantee the hybrid nature of F1 seed. Several technologies ranging from manual emasculation to genetic transformation are used to inhibit pollen production in mother plants. In this review, we examine the principles underlying strategies like genetically determined systems (genic male sterility, cytoplasmic–genic male sterility, self-incompatibility) and other methods (manual emasculation, chemical-hybridizing agents) in different species, considering the benefits and drawbacks of their adoption. Finally, we present the current state of the art for vegetable hybrid seed production.